(untitled) (Bangladesh Journal of Scientific and Industrial Research, 2007)
A study was conducted at the Farming Systems Research and Development (FSR&D) site of Bangladesh Rice Research Institute (BRRI) during kharif-I, 1999 to find the agronomic management followed for lady’s finger cultivation by the different categories of farmers and to understand its production, consumption and disposal pattern together with its economy. Technical knowledge was provided to the farmers for growing lady’s finger. Farmers grew the crop with their own management and resources. Variation was found in the date of sowing, rate of fertilizer application and number of irrigation. The highest pod yield was associated with better agronomic management that resulted higher gross margin. Lady’s finger production, consumption and selling were increased from April to June with a peak in the month of June. Lady’s finger consumption was highest per head in case of medium farmer and was decreased from medium farmer to marginal one. The utilization of money earned from lady’s finger selling followed a dissimilar pattern in different categories of farmers. Cultivation of lady’s finger might be an option for meeting the requirement of vegetable consumption, income generation and fulfilling the diversified demand of different category of farmers. Bangladesh J. Sci. Ind. Res. 41(1-2), 15-22, 2006